Quality of Life of Hypertensive Patients with Candesartan and Candesartan-Amlodipine Combination Therapy at a Governmental Hospital in Yogyakarta, Indonesia - Faridah Baroroh (Journal of Global Pharma Technology, 2020)
Many types of antihypertensive drugs produce different efficacies, and their use in therapy is often associated with unpleasant side effects that diminish the quality of life. This prospective cohort study intended to compare the impacts of two different treatments, namely candesartan and the combination of candesartan and amlodipine, on the quality of life of hypertensive outpatients at a government hospital in Yogyakarta, Indonesia. Starting with preliminary data survey, the analysis continued to measuring the quality of life of 100 respondents, which had met the inclusion and exclusion criteria, after three months of therapy. In the EQ5D questionnaire on quality of life, the EQ5D dimension was converted to EQ5D Index. The data analysis involved chi-square and correlation tests. The EQ-5D index ranged from 0.540 to 0.933 with an average of 0.819. Based on gender and complications, the quality of life of the patients who underwent candesartan therapy was not significantly different from those who took candesartan and amlodipine (p> 0.05). Meanwhile, based on age, occupation, income, and education, a significant difference was detected (p <0.05). The quality of life significantly correlated with age, employment, income, and education (p <0.05) but insignificantly with gender and complications (p> 0.05). As a conclusion, candesartan and candesartan-amlodipine therapies do not affect the quality of life of the patients differently, and the type of treatment is a factor that does not significantly affect the quality of life of the patients (RR; 95% CI = 1.135; 0.812-1.587). Keywords: Quality of life, Candesartan, Candesartan-Amlodipine, Hypertension, Outpatient.